The Future of Retail: Omnichannel Strategies for a Seamless Customer Journey - Sjukun Sjukun (International Journal of Economics Development Research (IJEDR), 2024)
This study explores the relationships between Omnichannel Strategy, Customer Engagement, Technology Adoption, and Customer Satisfaction within the context of Tokopedia users. Utilizing a quantitative research design, data was collected from 100 Tokopedia users in Medan through an online survey and analyzed using SmartPLS. The findings reveal that Omnichannel Strategy and Customer Engagement independently have a significant positive impact on Customer Satisfaction, while Technology Adoption also contributes substantially to enhancing Customer Satisfaction. Notably, the interaction between Omnichannel Strategy and Technology Adoption significantly amplifies Customer Satisfaction, highlighting the importance of integrating advanced technologies into omnichannel approaches. Conversely, the interaction between Omnichannel Strategy and Customer Engagement shows an insignificant effect on Customer Satisfaction, suggesting challenges in coordinating engagement efforts across multiple channels. These results emphasize the need for businesses to strategically combine omnichannel approaches with technology adoption to maximize customer satisfaction, while carefully managing engagement strategies across platforms.